Dietary patterns before and during pregnancy and birth outcomes: a systematic review. (28th March 2019) - Raghavan, Ramkripa; Dreibelbis, Carol; Kingshipp, Brittany L; Wong, Yat Ping; Abrams, Barbara; Gernand, Alison D; Rasmussen, Kathleen M; Siega-Riz, Anna Maria; Stang, Jamie; Casavale, Kellie O; Spahn, Joanne M; Stoody, Eve E
ABSTRACT: Background: Maternal diet before and during pregnancy could influence fetal growth and birth outcomes. Objective: Two systematic reviews aimed to assess the relationships between dietary patterns before and during pregnancy and 1 ) gestational age at birth and 2 ) gestational age- and sex-specific birth weight. Methods: Literature was searched from January, 1980 to January, 2017 in 9 databases including PubMed, Embase, and Cochrane. Two analysts independently screened articles using predetermined inclusion and exclusion criteria. Data were extracted from included articles and risk of bias was assessed. Data were synthesized qualitatively, a conclusion statement was drafted for each question, and evidence supporting each conclusion was graded. Results: Of the 9103 studies identified, 11 [representing 7 cohorts and 1 randomized controlled trial (RCT)] were included for gestational age and 21 (representing 19 cohorts and 2 RCTs) were included for birth weight. Limited but consistent evidence suggests that certain dietary patterns during pregnancy are associated with a lower risk of preterm birth and spontaneous preterm birth. These protective dietary patterns are higher in vegetables; fruits; whole grains; nuts, legumes, and seeds; and seafood (preterm birth, only), and lower in red and processed meats, and fried foods. Most of the research was conducted in healthy Caucasian women with access to health care. No conclusion can be drawn on the association between dietary patterns during pregnancy and birth weight outcomes. Although research is available, the ability to draw a conclusion is restricted by inconsistency in study findings, inadequate adjustment of birth weight for gestational age and sex, and variation in study design, dietary assessment methodology, and adjustment for key confounding factors. Insufficient evidence exists regarding dietary patterns before pregnancy for both outcomes. Conclusions: Maternal dietary patterns may be associated with a lower preterm and spontaneous preterm birth risk. The association is unclear for birth weight outcomes.